Digitalization and supply chain management: impact assessment of healthcare technology implementation on service delivery in public hospitals, Lagos, Nigeria - Ibikunle, Busayo (Journal of Social Sciences and Management Studies, 2024)
The study examined digitalization and supply chain management: assessing healthcare technology implementation for service delivery in Lagos General Hospital, Nigeria. It employed both qualitative and quantitative techniques. It analysed 293 questionnaires using multiple-regression, and Pearson. It used thematic to analyse data from interview and focused group discussion. The results showed a value of 3.28, with a standard deviation of 1.46, indicating the effectiveness of healthcare technology in general hospital. The H2 (R2 =.078, R = 278, F (2,290) = 12.19; p<.001) revealed digitalization-supply chain management have effect on Service-Delivery. The H3 (t = 3.71; B =.234; p<.001) revealed SCM can have an effect on achieving Sustainable-Development-Goal3. H4 (r =.070; p >.05) Revealed E-Medical Record does not have an effect on death rate in Lagos State, Nigeria. The study recommended, among other things, that all government and private healthcare facilities should harmonise EMR through SCM.